Massive open online courses for nurses' and healthcare professionals' continuous education: a scoping review. (15th April 2021) - Longhini, Jessica; Rossettini, Giacomo; Palese, Alvisa
Abstract : Aim: To map the main characteristics of massive open online courses, and their effectiveness, facilitators and barriers in continuing education among nurses and other healthcare professionals. Background: Online continuous education attracted new attention among educators and managers with regard to how to best design, implement it and evaluate its effectiveness. Introduction: No studies to date have mapped the state of research on massive open online courses and the facilitators promoting their effectiveness in continuing education. Methods: A scoping review performed in 2020 by following the Preferred Reporting Items for Systematic reviews and Meta‐analysis extension‐Scoping Reviews. Electronic databases were searched for primary and secondary studies, written in English. Identified barriers/facilitators were categorized using a content analysis. Results: Of the 1149 studies, 31 were included, and the majority had an explorative research design. Massive open online courses documented to date are characterized by their (a) developers' countries and providers, mainly the United Stated and universities, respectively; (b) variety of teaching methods and contents, including infectious diseases; (c) using both qualitative and quantitative assessment methods; and (d) multidisciplinary target audience ranging from 40 to 83 000 participants, including nurses. Facilitators of and barriers to effectiveness depend on their pedagogical background, appropriate course design, delivery and implementation as well as on the learners' profile. Discussion: Studies available to date are mainly based on experiential projects. A variety of strategies promoting massive online courses' effectiveness have emerged. Conclusion: Some public health issues may benefit from massive education, as a unique system promoting a quick and effective continuous education. Implications for Nursing/Health/Social Policy: Clinical nurses, nurse managers and educators should consider available evidence on massive online courses' when making decisions on which strategy to use to maintain competencies. Moreover, as a public health tool, massive online courses should be derived from a strong cooperation between political, scientific and professional bodies.